2009
DOI: 10.2215/cjn.01330209
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of the Non-Nephrotic Membranous Nephropathy Patient

Abstract: Background and objectives: Although early studies suggest that patients with idiopathic membranous nephropathy (MGN) and subnephrotic range proteinuria overall do well, these studies were small and follow-up was short or difficult to discern.Design Conclusions: Patients with MGN and sustained subnephrotic range proteinuria have an excellent prognosis. Conservative management with close monitoring is recommended given the difficulty predicting which patients will develop nephrotic range proteinuria and then pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
93
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 19 publications
6
93
0
2
Order By: Relevance
“…Similar results were published by Marx et al [16] and Yoshimoto et al [30], while Heeringa et al [10] reported serum creatinine as an independent predictor. We found baseline 24-hour proteinuria as an unfavorable predictor for RF in univariate analysis and multivariate analysis, which is consistent with other studies [11,16,30].…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were published by Marx et al [16] and Yoshimoto et al [30], while Heeringa et al [10] reported serum creatinine as an independent predictor. We found baseline 24-hour proteinuria as an unfavorable predictor for RF in univariate analysis and multivariate analysis, which is consistent with other studies [11,16,30].…”
Section: Discussionsupporting
confidence: 93%
“…Some of the previous studies reporting SR in untreated IMN patients included an important number of patients presenting with non-nephrotic proteinuria, 21 a clinical presentation with an inherently good prognosis. 1,13,22 Our study also provides interesting and previously not well characterized features of SR. Confirming previous studies 16 -20 most SR appeared during the first 2 years after diagnosis.…”
Section: Discussionmentioning
confidence: 58%
“…In particular, treatment with angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II type 1 receptor antagonists (ARBs) in patients with nephrotic syndrome was uncommon, whereas they are now widely prescribed in patients with proteinuric nephropathies. Furthermore, some of the studies reporting SR in untreated IMN patients included an important number of patients presenting with non-nephrotic proteinuria, 21 a clinical presentation with an inherently good prognosis, 22 and recent data about clinical characteristics, predicting factors, and long-term outcome in IMN are scanty. The aim of the present retrospective study was to report the clinical features and outcome of 328 patients with biopsy-proven IMN, in whom an initially conservative therapeutic approach, without corticosteroids or other immunosuppressive agents, was followed.…”
mentioning
confidence: 99%
“…The value of adding angiotensin II blockade to a conservative regimen, with the intent of fostering a "spontaneous" remission, is not firmly proven, and little benefit of such treatment is observed in patients presenting with proteinuria .10 g/d (19), but it may augment spontaneous remissions when lower levels of proteinuria are present (20). Conservative management is justified for patients with persistent subnephrotic proteinuria.…”
Section: When Should a Specific Treatment For Idiopathic Mn Be Started?mentioning
confidence: 99%
“…Conservative management is justified for patients with persistent subnephrotic proteinuria. However, these patients should be monitored because approximately 60% of them may progress to nephrotic syndrome (20). Patients with proteinuria persistently (.6 months) .4 g/d have an approximately 55% probability of developing ESRD within 10 years, and those with persisting proteinuria .8 g/d and/or abnormal levels of serum creatinine have an approximately 66%-80% probability of developing ESRD within 10 years (21).…”
Section: When Should a Specific Treatment For Idiopathic Mn Be Started?mentioning
confidence: 99%